Pengaruh Perceived Trust, Perceived Value Dan Brand Image Terhadap Repurchase Intention - Raja, Muhammad Rizali; Yuana, Pusvita (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2024)
The objective of this research is to identify the effects of perceived trust, perceived value, and brand image on the repurchase intention of Shopee application users in Malang city. This explanatory research corroborates the causal relationship between its variables through hypothesis testing. Using non-probability sampling method and purposive sampling technique with the criteria of person with the minimum age of seventeen years who have made at least one purchase through Shopee or have the intention to buy products via the application, 115 people were selected as the respondents. The data was analyzed using multiple linear regression, and the hypothesis testing was conducted using t-test; all of which were performed in SPSS 25. The results of the hypothesis testing have led to findings that (1) perceived trust significantly influences repurchase intention, (2) that perceived value significantly affects repurchase intention, and that (3) brand image has a significant impact on repurchase intention. Therefore, it can be concluded that this research on the application users finds that all independent variables are influential for the dependent variable. This implies a suggestion that the application company should conduct maximum supervision on the security and the personal data of its users so that they continue to feel safe while shopping online without being worried about security and privacy issues and should focus on its unique service improvement such as giving more points and other advantages.   Abstrak   Penelitian ini dilakukan dengan tujuan untuk berfokus pada mengetahui pengaruh Green Marketing, Green Perceived Value, dan Green Brand Image terhadap Purchase Intention pada Konsumen Brand H&M di Kabupaten Gresik. Pengaruh yang dimaksudkan pada penelitian ini ialah pengaruh yang terjadi baik secara langsung maupun secara tidak langsung antara variabel independent terhadap variabel dependen. Jenis penelitian ini adalah penelitian eksplanatif menggunakan pendekatan kuantitatif. Penelitian ini menggunakan data sampel sebanyak 140 responden yang berasal dari populasi konsumen Brand H&M di Kabupaten Gresik. Analisis data yang digunakan adalah IBM SPSS 25.0. Hasil penelitian yang dilakukan menggunakan beberapa rangkaian pengujian menunjukkan hasil yang dapat disimpulkan bahwa Green Marketing tidak mampu untuk berkontribusi terhadap Purchase Intention, Green Perceived Value mampu memiliki hubungan kontribusi yang positif terhadap Purchase Intention. Demikian pula dengan Green Brand Image mampu mendorong hubungan yang terjadi secara positif terhadap Purchase Intention.